Polygamy in Islamic Jurisprudence and the Law of Indonesia | حكم تعدد الزوجات في الفقه الإسلامي والقانون الإندونيسي - Yuli Yasin (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2009)
This research deals with polygamy in Compilation of Islamic Law in Indonesia(KHI) that considered as a basic reference by judges of the Islamic court in theirdecision, comparing with Islamic jurisprudence. KHI states that poliygamy isnot allowed for Indonesian Muslims except in certain conditions. Theresearcher attempts to analize to what extent the conditions agree with theIslamic jurisprudence.